The impact of freelance work on the attitudes and working habits of Generation Z in Vietnam - Ha, Tam Anh; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The purpose of this thesis is to examine how the attitudes and work habits of people from Generation Z in Vietnam are impacted by freelancing in the Vietnamese market. The study explores both the positive and negative impacts of freelance work on the part of young individuals and focuses on understanding the pain points and difficulties of this generation. Additionally, there is a comparison with other generations regarding attitudes and working habits between traditional and freelance work. The study uses a qualitative approach, including a questionnaire with fifteen in-depth interviews of individuals who have engaged in traditional and freelance work. This research will give valuable findings for young people and employers in the context of a personalizing society in the developing country of Vietnam. Recommendations and summaries are based on the results of the questionnaire and interviews.
Vedoucí práce: Kateřina Legnerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses